Enhanced electrochemical properties of Co3O4 with morphological hierarchy for energy storage application: A comparative study with different electrolytes. (January 2021) - Chatterjee, Mahasweta; Sain, Sumanta; Roy, Atanu; Das, Sachindranath; Pradhan, Swapan Kumar
Abstract: A facile hydrothermal route synthesizes Co3 O4 nanocrystals with urchin spine-like morphology. Structure and microstructural characterizations of the sample are carried out. Electrochemical properties have been explored in the presence of different electrolytes. In order to find out the best electrolyte, three electrolytes (Na2 SO4, NaOH and Na2 SO4 with Hq) of fixed concentration (1 M) are used to record the cyclic voltammetry data. In the presence of Na2 SO4 as an electrolyte, specific capacitance becomes 218 F g −1, possibly because of low ionic conductivity of SO4 2−, higher charge transfer resistance. When NaOH and Na2 SO4 (with Hq) are used as electrolytes, high specific capacitances of 1720 F g −1 and 2433 F g −1 respectively are obtained due to extra pseudocapacitive effect of redox reaction. It is worth noting that the semicircle diameter in the EIS plot is highest for Na2 SO4 and lowest for Na2 SO4 (with Hq) electrolyte. The Rct value depends on the type of electrode and the interaction between electrolyte ions with the electrode. Highlights: Urchin spine-like Co3 O4 nanocrystals are synthesized by a facile hydrothermal route. To find out best electrolytes, three different electrolytes are used. High sp. capacitances of 1720 F g −1 and 2433 F g −1 achieved for two different electrolytes. Specific capacitance value correlated well with Rct value of different electrolytes.